IRON INTAKE AND STRESS LEVEL WITH PRIMARY DYSMENORRHEA IN HIGH SCHOOL STUDENTS - Muawanah, Nur; Kurniawati, Meti; Alamsyah, Putri Rahmah; Widhi, Anisa Sekar (Media Gizi Indonesia, 2025)
One of the signs of puberty experienced by young women is menstruation, some young women experience pain known as dysmenorrhea during menstruation. Iron is one of the essential nutrients for adolescent reproduction, and its deficiency can increase the risk of dysmenorrhea. Stress can also affect Dysmenorrhea, as stress can lead to hormonal imbalances and the secretion of prostaglandin hormones produced by stress. The purpose of this study was to analyze the relationship between iron intake and stress levels with the incidence of primary dysmenorrhea in adolescent girls at PB Soedirman Islamic High School Bekasi. This study uses an observational analytic method with a cross-sectional design, and data collection using consecutive sampling techniques with 100 respondents. Data were collected through semi-quantitative food frequency questionnaires (SQ-FFQ) and Perceived Stress Scale (PSS) and determining the incidence of dysmenorrhea using dysmenorrhea questionnaires. The results measured by Chi-square test, showed p-values for iron intake (0.010) and stress levels (0.002). This study found a significant correlation between stress levels and iron intake in adolescent girls in PB Soedirman Islamic High School Bekasi.